The HuMAnS toolbox, a homogenous framework for motion capture, analysis and simulation - Wieber, P. B.; Billet, F.; Boissieux, L.; Pissard-Gibollet, L. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
Primarily developed for research needs in humanoid robotics, the HuMAnS toolbox (for Humanoid Motion Analysis and Simulation) also includes a biomechanical model of a complete human body, and proposes a set of versatile tools for the modeling, the capture, the analysis and the simulation of human and humanoid motion. This set of tools is organized as a homogenous framework built on top of the numerical facilities of Scilab, a free generic scientific package, so as to allow genericity and versatility of use, in the hope to enable a new dialogue between direct and inverse dynamics, motion capture and simulation, all of this in a rich scientific software environment. Noticeably, this toolbox is an open-source software, distributed under the GPL License.